Istifâdatu Dauri Qismi Al Da’wah Al Thullâbî Lilbanât Fî Tanmiyati Al Da’wah Ladâ Thâlibât Jâmi’ati Al Râyah - Annisa Pratiwi; Husnul Khatimah (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2022)
ملخص البحث الدعوة هي أهم نشاط يجب أن يقوم به كل مسلم في دعوة الناس إلى الخير ومنع الشر. في عصر الألفية هذا، يصبح المراهقون أهم دور في الترويج للدعوة من خلال استخدام المرافق المحيط بهم، طالما أنَّ هذه المرافق لا تتعارض مع العقيدة والشريعة الإسلامية، مثل الاستفادة من دور قسم الدعوة والتعليم الجامعي بمصدر واضح وهدف محدد. كان الهدف من هذه الدراسة هو تحديد ومعرفة دور قسم الدعوة والتعليم الطلابي للبنات بجامعة الراية في تطور القيادة كإطار لتمكين وتدريب الطالبات لتشكيل الأخلاق الكريمة. تستخدم الباحثة هذا البحث نهجًا كميًّا مع طريقة بحث دراسة حالة على العديد من أعضاء هذا القسم والمصادر الأولية التي تمَّ الحصول عليها من المقابلات المباشرة مع رئيسة ونائبة رئيسة القسم. تتضمن محاولة تحليل الدعوة التي تتمّ ما يلي: مصادر الاتصال، تمَّ تسليم الرسالة؛ والتغييرات في المواقف التي تحدث. تشير هذه الدراسة إلى أنَّ هذا القسم لا يزال يتطلب بذل جهود لتحقيق الأهداف المخططة وغير المحققة. وكذلك الحال مع الطالبات اللاتي يحتجن إلى توجيههنَّ في تشكيل الشخصية الإسلامية. Abstract Da’wah is the most important activity that must be carried out by every Muslim in inviting the people to do good and prevent evil. In this millennial era adolescents become the most important role in promoting da’wah by the use facilities that are around them, as long as these facilities do not conflict with Islamic creed and sharia, such as the utilization of the role of the campus missionary division with a clear source and exact target. The purpose of this study was to determine the role of the STIBA Ar Raayah student missionary division in the decelopment of leadership as a framewowk of empowerment and coaching for female students to shape the morals of karimah. This research uses a quantitative approach with a case study research method on several members of the division and primary sources obtained from direct interviews with the chairman and vice chairman of the division. Trying to anayze the da’wah communication carried out includes: communication sources; message delivered; and attitude changes that iccur. The results of this study indicate that this division still requires efforts to achieve the planned and unmet targets. Keywords: Da’wah, Utilization, Development of Da’wah, Division Role.